Pengembangan Program Kesehatan Reproduksi Remaja untuk Meningkatkan Pengetahuan dan Kesadaran Remaja tentang Kesehatan Reproduksi - Reffita, Lea Ingne (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Adolescents are an age group vulnerable to reproductive health problems due to a lack of knowledge and awareness regarding physiological changes, the risk of sexually transmitted infections, teenage pregnancy, and risky sexual behavior. This community service research aims to develop a reproductive health program for adolescents in [location name] with a focus on increasing their knowledge and awareness. Activities were conducted using participatory methods, including interactive counseling, group discussions, and the provision of educational media in the form of brochures, posters, and modules. Evaluation was conducted through pre- and post-tests and active participant observation of adolescents. Results showed a significant increase in adolescent knowledge scores, from an average of 55% to 85%, as well as increased awareness regarding the importance of maintaining reproductive health. This program has proven effective and has the potential to become a model for sustainable reproductive health education among adolescents.